TORQUE AND SQUARE-ROOT-FUNCTION - Peter Kepp (European Scientific Journal, ESJ, 2013)
• A new view on the root-function.• Numbers used in their particular, mathematical function – as the value of a measure in a unit.• By example, a view on that multiplications (genuine multiplication) which produce new units.• The way to understand why the square-root of a negative radicand is solvable by an operational way and why we have to define the root-function new.• Altogether the first step of a restructuring of whole the numerical mathematics – a reform of the signs